The impact of remanufacturing on total inventory cost and order variance - VAYVAY, ÖZALP (ELSEVIER SCI LTD, 2014)
In this study, a hybrid system with both manufacturing and remanufacturing options is considered. Traditional (without remanufacturing), and push- and pull-controlled hybrid systems are compared using a simulation model under different demand and return rates, manufacturing and remanufacturing lead times, setup and holding cost rates. Production order variances that are used to measure the bullwhip effect, and total recoverable and serviceable inventory costs are considered as the main performance indicators. In terms of total recoverable and serviceable inventory cost, our findings point out that hybrid pull-control policy outperforms the hybrid push-control policy. To measure the performance of a traditional system in contrast to push- and pull-controlled hybrid systems, total serviceable inventory costs are compared. It is noted that hybrid push- and pull-control policies have lower serviceable inventory costs than a traditional system. Especially for higher remanufacturing return rates, the cost performance of hybrid systems is even better. Furthermore, hybrid production systems have lower manufacturing and remanufacturing order variances than a traditional system.
Keywords: Remanufacturing; Hybrid push and pull systems; Order variance; PRODUCT RECOVERY; SYSTEM; PERFORMANCE; BULLWHIP; STRATEGIES; POLICIES; ISSUES; MODEL